Pengaruh Store Atmosphere dan Price Discount terhadap Impulsive Buying pada Butik Fyllo Closet di Kota Pematangsiantar - Mei Sarah Harahap; Dahrul Siregar (Mahesa Research Center, 2022)
This study aims to determine the effect of store atmosphere and price discounts on impulse buying at the Fyllo Closet Boutique in Pematangsiantar City. This research is a type of descriptive research using a quantitative approach. The sampling technique used purposive sampling method and how to determine the sample size using the slovin method with a total sample of 110 respondents. The data collection technique used an online questionnaire through a google form which had been tested for validity and reliability. Data analysis technique using multiple linear regression. The results showed that: (1) Store Atmosphere had a positive and significant effect on Impulse Buying. (2) Price discount has a positive and significant effect on Impulse Buying. (3) Store Atmosphere and Price Discount have a positive and significant impact on Impulse Buying.